Single-layer continuous versus double-layer continuous suture in colonic anastomoses: a randomized multicentre trial (ANATECH trial) - Herrle, Florian; Diener, Markus K.; Kienle, Peter; Weiß, Christel; Post, Stefan (Journal of gastrointestinal surgery, 2016)
Purpose: Apart from stapling methods, single- or double-layer continuous hand sutures are established techniques for colonic anastomoses. It is unclear which hand suture technique has superior anastomotic safety. This randomized trial evaluated the incidence of postoperative complications depending on anastomosis technique. Methods: This multicentre randomized trial enrolled adult elective patients between February 2004 and June 2012 in four German university hospitals. Primary endpoint was incidence of clinical anastomotic leakage until 3 months postoperatively. Estimated sample size was 768 randomized patients. Main secondary endpoints were duration of anastomotic suture, postoperative morbidity and stool patterns at 3-month follow-up. Patients and postoperative outcome assessors were blinded to the group assignment. This trial is registered (NCT00996554). Results: Due to slow recruitment, the trial was stopped prematurely. Two hundred fifty-two patients (129 to single-layer suture anastomosis (SLA), 123 to double-layer suture anastomosis (DLA)) were randomized and analysed. Nine patients (3.6 %) were lost during follow-up. Exploratory primary endpoint analysis by intention-to-treat principle showed no significant difference for clinical anastomotic leakage between suturing techniques (SLA, 4 of 129 (3.1 %) vs. DLA, 6 of 123 (4.9 %), p = 0.532). Secondary endpoint analysis showed on average a 6-min shorter suture duration for SLA than DLA (18 min (4-49) vs. 24 min (8-50), p < 0.001). At 3-month follow-up, subjective well-being and stool patterns were not significantly different between groups. Conclusions: The present study did not reach sufficient power and cannot confirm whether both techniques might be equally or if one technique might be superior. Exploratory analysis suggests that in elective colonic resections, the single-layer continuous hand suture technique may be equally effective as the double-layer technique regarding incidence of anastomotic leakage, length of hospital stay, overall postoperative complications, subjective short-term well-being and stool patterns. Lessons learned from this trial course are summarized.
Gesehen am 29.01.2019
Published online: 2 November 2015